Influence of conditioning on the behaviour of alluvial soils with cobbles. (February 2020) - Carigi, Andrea; Luciani, Andrea; Todaro, Carmine; Martinelli, Daniele; Peila, Daniele
Highlights: EPB conditioning is critical in high-cobble content soils. Cobble segregation in bulk chamber may lead to major problems. Slump test is suitable for soils with maximum particle diameter of 40 mm. The interaction between the conditioned matrix and cobbles is important. Tilt Slidind Test evaluates the interaxtion of cobbles with the matrix. Abstract: Many cities are built on alluvial soils and the excavation for services and tunnels become more important as the surface becomes more congested. Today EPB shields excavation is the leading technology for tunnel excavation in urban context due to the limited space on the surface, the noise, vibration and safety requirements. In cases with high cobbles content optimization of the conditioning is necessary in order to allow a homogeneous flow of cobbles in the pressure chamber and along the screw conveyor. This should be assessed through a test that evaluates the reduction of the gravitational separation of the larger elements in the chamber and the risks of face instability, tool breakage and water inflow through the screw conveyor. This paper presents a new test to evaluate the homogeneity of flow of cobbles in the excavated mass. The development of the test is described along two test campaigns and the improvements achieved in the second campaign are explained. Two indexes are proposed to assess the suitability of conditioning.